Entangled cetacean events in El Salvador - Castaneda, Melvin Giovanni; Ransome, Nicola L.; Benito, Paula C.; Pineda, Luis; Martínez de Navas, Elba (Universidad de El Salvador. Secretaría de Investigaciones Científicas, 2023)
Entanglement in fishing gear is recognized as the main modern threat to cetacean populations worldwide. The following is the first evidence of interactions between artisanal marine-coastal fisheries and cetaceans along the Pacific coast of El Salvador. Between 2017 and 2022, five entanglement events were recorded, two in oceanic dolphin species, Stenella longirostris and S. attenuata, three cases of humpback whales, Megaptera novaeangliae, one of them was a mother and a dependent calf, entangled in the same fishing gear. These five incidents were documented in western El Salvador, near the Port of Acajutla and constitute the first report of cetacean entanglement in the country, including a case affecting a population of endangered migratory whales and a threatened dolphin species. Of note, two cases of live entanglement involved attempts/ successful release of the animals by local volunteer fishermen, rangers, and naval force personnel not trained in cetacean rescue. This report highlights the need to manage and mitigate fishing interactions with cetaceans in El Salvador, including training of rescue teams, to reduce the threat of cetacean entanglement and risk to human life during rescue attempts El enredo en las artes de pesca es reconocido como la principal amenaza moderna para las poblaciones de cetáceos a nivel mundial. A continuación, se presenta la primera evidencia de interacciones entre las pesquerías artesanales marino-costeras y los cetáceos a lo largo de la costa del Pacífico de El Salvador. Entre los años 2017 y 2022, se registraron cinco eventos de enredo, dos en especies de delfines oceánicos, Stenella longirostris y S. attenuata, tres casos de ballenas jorobadas, Megaptera novaeangliae, uno de ellos fue una madre y una cría dependiente, enredadas en el mismo arte de pesca. Estos cinco incidentes fueron documentados en el oeste de El Salvador, cerca del Puerto de Acajutla y constituyen el primer informe de enredo de cetáceos en el país, incluyendo un caso que afecta a una población de ballenas ...